The Relationship Between Creativity and Student Learning Achievement in Class XI Phase F of SMA Negeri 1 Bonjol, Pasaman Regency - Marnisa, Fadilla; Suryadi, Suryadi; Usman, Citra Imelda (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research was motivated by the existence of students who did not ask the teacher even though they did not understand the learning material and there were students who did not carry out remediation on their report card grades. The aim of this research is to describe: 1) The learning creativity of students in class XI Phase F SMA N 1 Bonjol, 2) The learning achievement of students in class Phase F SMA N 1 Bonjol. This research was conducted using quantitative descriptive methods with correlation analysis. The population of this study were students in class XI Phase F of SMA N 1 Bonjol for the 2023/2024 academic year, totaling 323 students. This sampling technique was carried out using a purposive sampling technique, namely 71 students who became the research sample. And the data analysis techniques used are percentage and correlation tests. The results of this research show that the relationship between creativity and student learning achievement in class XI Phase F SMA N 1 Bonjol can be drawn as follows: 1) The learning creativity of students in class XI Phase F SMA N 1 Bonjol is in the high category. 2) The learning achievement of students in class XI Phase F SMA N 1 Bonjol is in the high category. 3) There is a relationship between creativity and student learning achievement in class XI Phase F SMA N 1 Bonjol, which is -0.46 with a fairly strong relationship coefficient. Based on the results of this research, it is recommended to guidance and counseling teachers that students are able to increase students' learning creativity so that students' learning achievements are higher.